(untitled) (Research, Society and Development, 2022)
This report aims to share the experience lived at “Health Work Education Program – PET-Saúde Interprofessionality” in secondary care by a tutorial group from the Federal University of Juiz de Fora campus Governador Valadares/MG (UFJF-GV). Therefore the Situational Diagnosis (SD) and the Situational Strategic Planning (PES) were carried out in order to achieve the objective image: Improve interprofessional communication making it more effective. The following interventions were carried out: Training of professionals at Occupational Health Referral Center (CEREST) and disclosure of CEREST. As a result, the following stood out: low adhesion of professionals due to the COVID-19 pandemic, institutional partnerships between the tutorial group and the Distance Education Center “(CEAD)” of Federal University of Juiz de Fora (UFJF) as well as the approximation of CEREST and the Communication Department “(SECOM)” of the county. The pandemic was a major limitation for the actions developed especially with regard to the adhesion of CEREST professionals to the training course. However one solution found was the expansion of the offer of this course until the end of 2021. As for the dissemination of CEREST on social network it is believed that the dissemination of its services has been of great importance since social networks are currently an efficient and accessible means of spreading information.